"Taking Care of Your Own": Parochialism, Pride of Place, and the Drive to Diversify Teaching. (October 2020) - Noonan, James; Bristol, Travis J.
As the student population in U.S. public schools becomes increasingly ethnoracially diverse, many school districts and hiring personnel have taken proactive approaches to recruiting teachers of color. The drive to diversify the teaching force is supported by a range of academic and nonacademic outcomes for students of color. Yet, many districts struggle with the recruitment and retention of teachers of color. One explanation for the slow pace of change, especially in districts with increasing diversity in its study body, is the presence of durable and parochial social networks in schools and districts that privilege the hiring of largely White alumni. Drawing on semistructured interviews with 65 participants in a small urban district and applying the analytic lens of bonding social capital, we examined these entrenched patterns of parochialism, and the extent to which parochial attitudes and behaviors intersect with race, to explain the incremental pace of change diversifying the teacher workforce.